KORELASI BEDAH BUKU DENGAN MINAT BACA GURU DI SDIT GHILMANI SURABAYA - Yuliani (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
The purpose of determined the relationship of book review among reading interest in teacher at SDIT Ghilmani. The data collection techniques are: (1) observation, (2) questionnaire, and (3) Interview. The sampling technique that saturated sampling where the whole populations were used as samples (40 teachers in SDIT Ghilmani. The data were analyzed by using Pearson Product Moment Correlation test. The results showed that (1) 65% of teachers said the program of book review at intervals of grades 24-26 with the minimum value is 23 and the maximum value is 29 (2) 70% interest in reading teacher included in the interval of values 46-50 with a minimum value of 38 and a maximum value of 50, (3) There was a book review with teacher reading interest with r value of 0.349 which was the correlation was weak; the surgical contribution to the book reading teacher at 12.18%, and t count 2.8422> t table 2,012 with α of 0.05. From the result above, it could be concluded that the book review could increase interest in reading books of teachers with motivated teachers to read, the time that should be devoted to reading, and the container for Exchanging experiences and knowledge among teachers that was expected to increase teachers’ competence.